The European Miracle - Reflections on the Economic History of the Early Modern Period - Schultz, Helga (Studia Historiae Oeconomicae, 2001)
In parallel with the great process of European integration, historians are working to create a European historical image. When they ask "Who are we? Where do we come from? Where are we going?", they bring to light the commonalities of history that can form the basis of a European identity.1 The boundaries of national histories that have been set up against each other since the last century must be overcome, as must the division of the continent into hostile blocs that dominated Europe's recent history.